2017
DOI: 10.7554/elife.21761
|View full text |Cite
|
Sign up to set email alerts
|

Humans treat unreliable filled-in percepts as more real than veridical ones

Abstract: Humans often evaluate sensory signals according to their reliability for optimal decision-making. However, how do we evaluate percepts generated in the absence of direct input that are, therefore, completely unreliable? Here, we utilize the phenomenon of filling-in occurring at the physiological blind-spots to compare partially inferred and veridical percepts. Subjects chose between stimuli that elicit filling-in, and perceptually equivalent ones presented outside the blind-spots, looking for a Gabor stimulus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…4. Since the mean blind spot diameter is around 4.5°2 2,25 , the center of the blind spots from our results is then 15.84° ± 0.96°, comparable to prior work, in which the blind spot locations are ranged between 14.33 • and 15.52°2 2,23,25 .…”
Section: Exp 2 Distance Calculation With Different Display Sizes and supporting
confidence: 89%
See 2 more Smart Citations
“…4. Since the mean blind spot diameter is around 4.5°2 2,25 , the center of the blind spots from our results is then 15.84° ± 0.96°, comparable to prior work, in which the blind spot locations are ranged between 14.33 • and 15.52°2 2,23,25 .…”
Section: Exp 2 Distance Calculation With Different Display Sizes and supporting
confidence: 89%
“…To tackle this issue, we devised a method in which we leverage the fact that the entry point of the optic nerve on the retina produces a blind spot where the human eye is insensitive to light. The center of the blind spot is located at a relatively consistent angle of α = 15° horizontally (14.33° ± 1.3° in Wang et al 22 , 15.5° ± 1.1° in Rohrschneider 23 , 15.48° ± 0.95° in Safran et al 24 , and 15.52° ± 0.57° in Ehinger et al 25 ). Given this, we can calculate an individual's viewing distance from simple trigonometry, as shown in Fig.…”
Section: The Virtual Chinrestmentioning
confidence: 96%
See 1 more Smart Citation
“…Traditionally, it is thought that much of peripheral vision is 'filled in' via top-down mechanisms (Komatsu, 2006). However, it has also been reported that people trust unreliable, filledin percepts more than percepts based on external input (Ehinger et al, 2017), suggesting that filling-in may not be the complete mechanism to explain peripheral phenomenology, and that decisional or metacognitive mechanisms are also involved. In our study, perhaps the findings of detection bias in the unattended periphery can also be interpreted as congruent with this account involving mechanisms at the decisional or metacognitive level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, inflation appears to be very similar to perceptual filling-in [10,59] . A recent study showed that filled-in percepts at the blindspot are rated as more reliable than perceptually equivalent, but externally veridical percepts [60] . Though, operationally speaking, this is not necessarily an inflation effect, it shows a similar pattern in which a percept that is based on a less veridical representation of the external world is actually granted a subjective boost.…”
Section: Inflation and The Richness Debatementioning
confidence: 99%